0223 Sleep during layovers of different lengths after long-haul flying across multiple time zones in different geographic directions. (25th May 2022) - Arsintescu, Lucia; Hilditch, Cassie; Gregory, Kevin; Kato, Kenji; Flynn-Evans, Erin
Abstract: Introduction: Long-haul pilots experience high levels of fatigue and circadian disruption due to long work hours and trans-meridian travel. The aim of this study was to characterize sleep timing and duration during layovers of different lengths after crossing multiple time zones. Methods: All pilots flying long-haul operations from a single airline were eligible to participate. While following their normal work schedule within airline operations, pilots collected data for ~2 weeks including at least two long-haul rotations, with rest days and layovers. Participants wore an Actiwach (Phillips Respironics) throughout the entire study period and completed a sleep diary (at bedtime and upon waking up). Based on the data, we categorized layovers as follows: layover type 1: 34 h after crossing five time zones in westward direction; layover type 2: 34 h, no time zone change; layover type 3: 55 h after crossing six time zones in eastward direction. Each flight left the home base at the same time of day (23:00) and the flight duration was between 10.5 and 12 h. We calculated descriptive statistics for each category. Results: Forty-four long-haul pilots participated in the study (5 female; mean age 44.25 ± 10.06 yrs; mean flight hours 9834.3 ± 5334.1 h). We found that for layover type 1, the mean sleep duration (h) per 24 h was 6.90 (±1.04), mean sleep efficiency (%) was 81.08 (±10.89), and mean Wake After Sleep Onset (WASO, min) was 33.23 (±20.42); for layover type 2, the mean sleep duration (h) per 24 h was 6.91 (±1.06), mean sleep efficiency (%) was 81.71 (±6.80), and mean WASO (min) was 30.10 (±11.00); for layover type 3, the mean sleep duration (h) was 7.07 (±1.32), mean sleep efficiency (%) was 83.93 (±6.04), and mean WASO (min) was 36.94 (±17.95). Conclusion: Our preliminary analyses showed that sleep duration and sleep efficiency were similar for the layovers of the same length regardless of time zone change. Additional analyses will be conducted to investigate sleep on additional layovers of different lengths and the effects of sleep obtained during layover on the performance and alertness on the return flights. Support (If Any): This research was supported by the NASA System-Wide Safety Program.